Genetic and histopathological characterization of Toxoplasma gondii genotypes isolated from free-range chickens reared in the metropolitan region of Rio de Janeiro state, Brazil - Casartelli-Alves, Luciana; Pereira, Sandro Antonio; Ferreira, Luiz Claudio; Macedo Couto, Rodrigo de; Schubach, Tania Maria Pacheco; Amendoeira, Maria Regina Reis; Silva, Rodrigo Costa da; Langoni, Helio [UNESP]; Millar, Patricia Riddell; Menezes, Rodrigo Caldas (Springer, 2021)
This study aimed to genetically characterize Toxoplasma gondii isolates obtained from free-range chickens reared in the metropolitan region of the state of Rio de Janeiro, Brazil, and to evaluate the morbidity and histological changes associated with these isolates in mice. A mouse bioassay was used to isolate T. gondii from a pool of tissue samples (brain, heart, and thigh muscles) collected from 163 chickens. The 36 isolates obtained were genetically characterized by restriction fragment polymorphism (PCR-RFLP) analysis of the SAG1, 5 '-3 ' SAG2, aSAG2, SAG3, BTUB, GRA6, c22-8, c29-2, L358, PK1, Apico, and CS3 genomic regions. Seventeen atypical genotypes were identified and nine of them were reported for the first time. All identified genotypes caused clinical signs and histological changes in mice, with the majority being associated with high cumulative morbidity (65%) and severe or very severe histological changes (76%). The exclusive identification of atypical genotypes, with a predominance of new genotypes, indicates great genetic diversity of T. gondii in the region studied. In addition, the finding that all identified genotypes caused clinical signs and often severe histological changes in mice suggests potentially relevant virulence of these strains.
Keywords: Bioassay; Chickens; Genotyping; Histopathology; Toxoplasma gondii; Morbidity